Analytical, experimental and numerical studies of fields in resonant cavities for microwave dielectric heating - Chow Ting Chan, Tse Voon (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph.D.) -- University of Stellenbosch, 1998.